Cervical joint positioning error and its association with cervical spine mechanics among undergraduate students - Malik, Reem Javed; Humaira Fareed; Farrah Qureshi; Fouzia Batool; admin (Journal of the Pakistan Medical Association, 2023)
A cross sectional analytical study was conducted from September 26 to December 28 2018 at Shifa Tameer-e-Millat University Islamabad with 111 undergraduate students aged 17-26 years as participants. The aim of the study was to establish the normative values of cervical joint positioning error (CJPE) and its association with cervical spine mechanics. Neck discomfort was measured using the neck portion of the “student specific Cornell Musculoskeletal Discomfort Questionnaire” (ssCMDQ) and CJPE was measured via cervico-cephalic relocation test using a goniometer. Non-parametric tests of significance were used because the data was not normally distributed in terms of normality testing. Normative values of CJPE were noted to be highest in flexion (9o±9o), rotation towards left (9o±6o) and right (8o±7o), extension (6o±8o), and lastly lateral flexion towards left (5o±7o) and right (5o±5o). Higher CJPE in all movements was observed among females; however, no significant statistical differences were observed (p>0.05). —Continue